Affectst of biotic and abiotic factors on some secondary metabolites in the root of Glycyrrhiza uralensis Fisch. (Mongolian Journal of Botany, 2024)
We aimed to examine the secondary metabolites in the root of G. uralensis from Eastern Mongolia and to see relationships between the content of these compounds depending on various factors such as region of plant growth, soil mechanic components, plant ontogenesis development stage, and whether it was cultivated or in the wild. G. uralensis root was collected from a total 9 soums of Dornod, Khentii, and Sukhbaatar provinces within 6 different ontogenesis stages. The contents of triterpene saponin (glycyrrhizin), and polysaccharide were determined by UV spectrometry using standard substances (Astragaloside IV, Glucose). The result of the research showed that the content of tritertenic saponins and polysaccharides in the root of G.uralensis were different depending on the stage of ontogenesis development as well as geographical location (p0.05). One of the interesting results of the study is that the total saponin (glycyrrhizin) was different (p